Completely queer the Gay and Lesbian encyclopedia - Hogan, Steve (Henry Holt, 1998)
"Completely Queer is a concise and balanced guide to the history, people, places, and ideas important to lesbian and gay communities worldwide. Linking a detailed chronology of homosexual life and achievement to nearly six hundred articles - ranging from "ACT UP" to "Lesbian Continuum," from "Military" to "Wilde"--It explores in depth more facets of today's gay and lesbian subcultures than any other one-volume reference work. Recognizing that the gay communities are far from static or homogenous in their politics, lifestyles, activities, and beliefs, authors Steve Hogan and Lee Hudson have created in this informative book an accessible volume. It features quotes, little-known facts, reading lists, and useful tables: one lists famous pseudonyms; another, gay detective novels."--BOOK JACKET. "Complete with more than 250 photos and illustrations, Completely Queer is the first guide to cover both lesbian and gay male points of view offering information on their common concerns as well as their different histories and interests."--Jacket.